ENTERPRENEURSHIP AND YOUTH UNEMPLOYMENT IN NIGERIA: THE MISSING LINK (Global Journal of Management and Business Research, 2011)
This paper examines youth unemployment in Nigeria and attributed the high unemployment to the disconnect between effective technical/vocational education and the development of an enterpreneurship culture. It proposed a drastic shift in policy from incremental curriculum to scientific and technical one that will promote student-centered learning with input from the private sector to reduce the present mismatch between labour demands and acquired skills. It concludes by proposing some strategies that can sustain an enterpreneural culture and reduction in youth unemployment.
Keywords: Unemployment; Youth enterpreneurship; Mismatch; Skill acquisition; Vocational/technical education